A Study on Beliefs in Domestic Sacred Objects of Thai Chinese in Talad Sub-district, Mueang District, Maha Sarakham Province - Kongtan, Pinnaporn; Sinthao, Suthasinee (Journal of Human and Society, Sisaket Rajabhat University, 2022)
The current study was conducted to study domestic sacred objects and beliefs related to domestic sacred objects of Thai Chinese in Talad sub-district, Mueang district, Maha Sarakham province. The samples were 10 families of Thai nationals with Chinese descent in the area. The data was collected by document analysis and interview, and they are presented using descriptive analysis. The results of the study indicate that most Thai Chinese living in the area are descended from Chaozhou region. Individual and traditional beliefs are mixed and presented in current practices among families of the Chinese in the area. Beliefs in sacred objects can also be considered as legacy transferred from generation to generation. People value, bless and fortune from ancient times. Giving sacred objects that could bring auspiciousness to life becomes a part of Chinese beliefs. To summarize, there are 2 aspects of sacred objects including 1) sacred objects as guardians of the house such as Di Zhuye (地主爷) and 2) sacred objects as bringers of fortune such as Pixiu (貔貅). These beliefs in sacred objects are influenced by the traditional beliefs among the Chinese people from time to time. Moreover, the traditional beliefs are also melted with Buddhism practiced among the Thai people in the area. It could be noted that the beliefs in scared objects of the Thai Chinese descendants have been changed from time to time with the influences of economy, time, society, and family.